Skills and HRD in the emerging global market perspective: A case of India - Awasthi, I. C. (Economic Journal of Development Issues, 2012)
Skills are regarded an important growth driver in knowledge based globalised economy. In most of the developed nations and fast growing economies have very high proportion of skilled work force, while the skill levels among the Indian work force is abysmally low and probably among the lowest in the world. One of the reasons for the low skill trained manpower is terribly low institutional training capacity and the vocational education and training systems as being too supply driven and far-removed from market demand. India has distinct advantage of young age-population with declining dependency ratio which is termed as ‘population dividend’ while the industrialized nations have ageing population with rising dependency ratio. This precisely gives India an advantage with huge competitive edge internationally. While industrialized nations will be facing acute shortage of skills with increasing dependency ratio, India can harness this huge potential if skill development initiatives fructifies in right direction which will then be in real sense a ‘population dividend’. If this opportunity is missed then it may well turn in to ‘demographic nightmare’ The paper aims at examining the skill issues in the context of globalization and seeks to scrutinize how the skilling efforts have moved on to central stage in order to reap the benefits. The paper explores the theme both from the demand and supply perspectives in a complex yet exciting global environment. DOI: http://dx.doi.org/10.3126/ejdi.v13i0.7210 Economic Journal of Development Issues Vol.13 & 14 2011, pp.51-64